1999
DOI: 10.1074/jbc.274.48.34350
|View full text |Cite
|
Sign up to set email alerts
|

Internalized Epidermal Growth Factor Receptors Participate in the Activation of p21 in Fibroblasts

Abstract: Regulated activation of the highly conserved RasGTPase is a central event in the stimulation of cell proliferation, motility, and differentiation elicited by receptor tyrosine kinases, such as the epidermal growth factor receptor (EGFR). In fibroblasts, this involves formation and membrane localization of Shc⅐Grb2⅐Sos complexes, which increases the rate of Ras guanine nucleotide exchange. In order to control Ras-mediated cell responses, this activity is regulated by receptor downregulation and a feedback loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 53 publications
6
100
0
2
Order By: Relevance
“…of at least three independent experiments performed in duplicate). These Rheb activation levels, particularly for serum-starved cells, are considerably higher than we and others have found for other wild type Ras-related proteins, including Ras and Rap 1: activation levels for serum-starved cells are generally in the range of 0.5 -8%, depending on the cell type, and activation levels for logarithmically growing or serum-stimulated cells are generally between 10 -18% (Scheele et al, 1995;Tian et al, 2000;von Lintig et al, 2000;Sharma et al, 1998;Prigent et al, 1996;Haugh et al, 1999;Satoh et al, 1990a,b). To perform experiments under identical conditions, we measured Rheb, Ras, and Rap 1 activation in serum-starved PC-12 cells, and found activation levels of 23+4%, 3+0.5%, and 5+0.7%, respectively.…”
Section: Activation Levels Of Endogenous Rheb and Of Transfected Rhebmentioning
confidence: 87%
“…of at least three independent experiments performed in duplicate). These Rheb activation levels, particularly for serum-starved cells, are considerably higher than we and others have found for other wild type Ras-related proteins, including Ras and Rap 1: activation levels for serum-starved cells are generally in the range of 0.5 -8%, depending on the cell type, and activation levels for logarithmically growing or serum-stimulated cells are generally between 10 -18% (Scheele et al, 1995;Tian et al, 2000;von Lintig et al, 2000;Sharma et al, 1998;Prigent et al, 1996;Haugh et al, 1999;Satoh et al, 1990a,b). To perform experiments under identical conditions, we measured Rheb, Ras, and Rap 1 activation in serum-starved PC-12 cells, and found activation levels of 23+4%, 3+0.5%, and 5+0.7%, respectively.…”
Section: Activation Levels Of Endogenous Rheb and Of Transfected Rhebmentioning
confidence: 87%
“…EGFR Signaling Compartmentation Protocol-Haugh et al (28,29) previously have shown that internalized EGFR can retain activity dependent on the binding properties of its ligand (Fig. 1A).…”
Section: Methodsmentioning
confidence: 99%
“…Images were false colored to grayscale; therefore, brightness correlates with increased fluorescence intensity and calpain activity. activated both from plasma membrane EGFR and endosomal EGFR (29). Obviously, the accessibility of focal adhesion components would differ greatly from these two sites.…”
Section: Figmentioning
confidence: 99%
“…The observation that the activated epidermal growth factor receptor can be detected on endosomes where it can activate Ras indicates that it is the receptor itself that needs to be internalized to initiate signaling (49,50). Furthermore, nerve growth factormediated signaling illustrates how one molecule can mediate dichotomous functions; the activated Trk receptor induces survival when at the plasma membrane, whereas it elicits differentiation of neurite outgrowth if internalized (51).…”
Section: Fig 7 Caveolae Inhibiting Agents Inhibit Igfbp-3 Nuclear Ementioning
confidence: 99%